Measurements of cross-country ski pole properties - Leppävuori, A.; Ohtonen, O.; Heikkinen, T.; Lemmettylä, T.; Linnamo, V. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Cross-country skiing is described as an equipment sport. Skis, poles and waxes are all essential for the end result. Contrary to the situation with skis, properties of the ski poles have been investigated very seldom. There are, however, methods for measuring forces produced by skier directly from poles (e.g. Rapp 2012) or with force plates under the snow (Vähäsöyrinki et al. 2008). Swaren et al. (2012) have developed measurement system for pole stiffness by loading the pole by screw. Present research project aimed to develop research methods for stiffness as well as for impact resistance measurements.